A new species of the broad-shouldered water strider genus Microvelia Westwood (Hemiptera: Heteroptera: Veliidae) from the Ogasawara (Bonin) Islands, Japan - Watanabe, Kohei (Zootaxa, 2023)
Microvelia (Picaultia) yoshitomii sp. nov., currently considered endemic to Haha-jima Island, Ogasawara (Bonin) Islands, Japan, is described. This new taxon was previously thought to be M. (P.) douglasi Scott, 1874, but has distinctly different morphological characteristics, including (1) proportional lengths of hind tarsomere II/I in both sexes approximately 1.1; (2) apex of male fore and middle tibiae strongly projected; (3) right paramere apically rounded and not markedly narrowed in lateral view, with ventral margin almost straight in lateral view.